Radiocarbon ages of sediment core MD05-2896 - Dong, Liang; Li, Li; Li, Qianyu; Wang, Hui; Zhang, Chuanlun L (PANGAEA, 2024)
To derive an age-depth models for the core radiocarbon ages were measured on the planktonic foraminifera species Globigerinoides ruber albus.